Potential Drug-drug Interactions and Adverse Drug Reactions Associated with Hydroxychloroquine - Singh, Arjun; Chaudhary, Richa; Verma, Prayas; Trivedi, Nilanchal; Shamim, Md. (Journal of Pharmacy Practice and Community Medicine)
Introduction: COVID-19 is a pandemic disaster and a health emergency of prime focus for all the world economies. Various prophylactic treatments are considered to combat the disease. Hydroxychloroquine drug is one such option that is given much attention as an armor against SARS COV-2 pandemic. Evaluation and assessment of drug interactions and ADRs is required from ethical concern to justify the use of HCQ on such large scale. Methods: We have performed an analysis of HCQ drug interactions on Micromedex®. We have reviewed literature of HCQ pharmacokinetic properties, ADRs/ ADEs and toxicities associated with the use of HCQ drug on PubMed, Google Scholar and CDC database. Results: There are around 180 drug interactions possible with HCQ. Out of them 13 are of contraindicated severity level and other 165 are of major severity and 2 of them are moderately severe. Most of the interactions are coupled with QT prolonging agents (170), Cardiac arrhythmias is possible with the concomitant use of at least 2 drugs, 4 drugs leads to Torsade de points. System organ level ADRs are also evaluated along with various precautions, warnings and contraindications. Conclusion: Currently various options are available such as chloroquine, HCQ- azithromycin, remdesivir, plasma therapy and many others in the pipeline. Majority of patients are asymptomatic, therefore blind use of HCQ should be prohibited. Considering DDIs and ADRs associated with HCQ use, it should be used under clinical care with emphasizing proper screening in cardiovascular co-morbid patients.
Keywords: Hydroxychloroquine; COVID-19; Drug Interactions; Adverse Drug Reactions; Micromedex®.